A pedagogy of weaving Nigerian Tiv a’nger into life writing, mobility and place: my travelling encounters as an international student retold - Oguanobi, Hembadoon Iyortyer (Université d'Ottawa / University of Ottawa, 2018)
This pedagogy of weaving the Nigerian Tiv a'nger into life writing, mobility and place blends in my experiences, cultures, geographical locations and stories. As I travel through and within countries as an international student, I draw from postcolonial and feminist scholars such as Anzaldua (1987), Bhabba (1994), Rushdie (2011) and Trinh (1994) in negotiating a hybrid space where my sense of belonging and home is continuously unsettled and negotiated. In this thesis, I use the a’nger as a metaphor for blending, merging and blurring text, identities, and questioning the conditions which produce stories, memories and events. In this auto/ethno/graphic pedagogy of weaving the Tiv a'nger into my encounters as a traveller, sojourner and mother, I am seeking to link my cultural background with my scholarship in the faculty of education and the faculty of law as a literary metissage that allows me to situate my narrative within broader sociopolitical discourses that query gender race and class issues (hooks, 2003; Fanon, 2008). I am guided by a desire to show that stories are research and that stories influence our movements as Africans in diaspora (Achebe, 1973; Wa Thiong’o, 1986). In drawing from the stories of my Tiv ancestors through African indigenous a’nger, I am guided by a quest to decolonize a space in academia to include other ways of knowing and being in the world. In retelling my stories, I open up conversations about the experiences of international students from Africa who relocate to other countries in the quest for continuous education. I use qualitative research methodologies such as auto/ethno/graphy (Douglas & Carless, 2013), bricolage (Kincheloe, 2005), metissage (Lionnet, 1991), multimodality (Morawski et al., 2016); and life writing (Hasebe-Ludt, Chambers & Leggo, 2009) to linger, tarry and trouble the sites between history and culture, home and abroad, us and them.
Keywords: life writing; curriculum; culture; pedagogy; belonging; hybridity; multimodality; Tiv; a'nger; traveller; identity; autoethnography; blending; diaspora